2016
DOI: 10.1016/j.drugpo.2016.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, vaping, eating: Is legalization impacting the way people use cannabis?

Abstract: Background In the context of the shifting legal landscape of medical marijuana, different methods of cannabis administration have important public health implications. How medical marijuana laws (MML) may influence patterns of use of alternative methods of cannabis administration (vaping and edibles) compared to traditional methods (smoking) is unclear. The purpose of this study was to determine if the prevalence of use of alternative methods of cannabis administration varied in relation to the presence of and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
160
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(170 citation statements)
references
References 33 publications
6
160
0
4
Order By: Relevance
“…Some participants used the same vaporiser for both products (switching cartridges between marijuana concentrates and nicotine solutions), while others reported owning devices for each. Although past studies showed that vaping was less common than smoking marijuana among a convenience sample of adults, 16 given the rapid growth of the marijuana vaporiser industry 23 24 and the growing popularity of electronic vaporisers, especially in states with legalised medical marijuana, 16 it is essential to study perceptions and practices related to electronic vaporisers for marijuana.…”
Section: Discussionmentioning
confidence: 99%
“…Some participants used the same vaporiser for both products (switching cartridges between marijuana concentrates and nicotine solutions), while others reported owning devices for each. Although past studies showed that vaping was less common than smoking marijuana among a convenience sample of adults, 16 given the rapid growth of the marijuana vaporiser industry 23 24 and the growing popularity of electronic vaporisers, especially in states with legalised medical marijuana, 16 it is essential to study perceptions and practices related to electronic vaporisers for marijuana.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although we did not have information about the methods of cannabis use among parents, which would affect the level of possible SCS exposure, recent evidence indicates the vast majority of cannabis use occurs via smoking, whereas edible forms account for <10% of use among US adults. 28,29 Future researchers need to obtain specific estimates of the degree to which level of exposure is changing among children in the home. Researchers using biomarkers of cannabis and tobacco exposure in children of different ages and in households implementing varying degrees of protection (eg, household smoking bans) are needed to advance the field.…”
Section: Discussionmentioning
confidence: 99%
“…No two LCL are exactly the same and analytical strategies that rely on yes/no LCL comparisons may obfuscate important underlying policy heterogeneity. The provisions within each LCL that dictate how cannabis is produced and distributed may impact important public health metrics such as rates of cannabis use and use disorder, average cannabis THC content, and utilization of new methods of cannabis administration (Borodovsky, Crosier, Lee, Sargent, & Budney, 2016; Pacula, et al, 2015; Sevigny, Pacula, & Heaton, 2014). Analyzing the effects of specific LCL provisions is necessary to clarify the true impact of cannabis legalization and to guide effective regulation of legal cannabis.…”
Section: Introductionmentioning
confidence: 99%